Rare metastasis of the urinary bladder from esophageal squamous cell carcinoma: a case report - Zhang, Chunlei; Chang, Dehui; Wang, Dongxing; Zuo, Jiale; Cao, Zhigang (Frontiers in Oncology, 2025)
BackgroundSquamous cell carcinoma (SCC) of the urinary bladder is rare, comprising less than 5% of all bladder cancers. There have been no previous reports of bladder SCC occurring as a metachronous metastatic tumor following curative resection for esophageal squamous carcinoma. This case report aims to address the challenges in treatment strategy posed by such occurrences by presenting a case of esophageal SCC with subsequent bladder metastasis.Case descriptionThe patient is a 57-year-old Asian male with a 40-year history of heavy smoking. In July 2020, he was diagnosed with esophageal SCC, staged as cT2N1M0, and underwent radical surgery followed by adjuvant radiotherapy, chemotherapy, and immunotherapy. Post-surgery, he remained asymptomatic with regular check-ups showing no recurrence until November 2021, when he presented with hematuria. An MRU indicated a solid lesion in the bladder, and biopsy confirmed poorly differentiated SCC. A partial cystectomy was performed, followed by chemotherapy. Despite stable initial follow-ups, elevated CEA and SCC-Ag levels later suggested recurrence, confirmed by PET-CT and pathological examination showing lymph node metastases around the esophagus and in the neck. Subsequently, chemotherapy combined with immunotherapy was recommended.ConclusionFor solitary metachronous metastatic SCC of the bladder following esophageal SCC, surgical resection combined with postoperative adjuvant chemotherapy can be a viable treatment option. Partial cystectomy may be feasible for patients without lymphatic spread and who wish to preserve bladder function. Tumor markers CEA and SCC-Ag have proven effective in monitoring postoperative metastasis and can serve as reliable indicators for tumor follow-up.